Analisa Kekasaran Permukaan Hasil Pemotongan Orthogonal Pada Proses Pemesinan Turn-Milling - Muhammad Iqbal; Yohanes Yohanes; Anita Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Turn-milling is a machining method with a system that combines turning and milling operations, which the work-piece and the cutting tool perform a rotating movement simultaneously. The purpose of this study was to investigate and analyze the surface roughness of the orthogonal cutting process in turn-milling machining. The rotary milling test was performed the orthogonal method and produces a final surface roughness that varies with tests carried out for the work-piece speeds and the feed speeds. The resulting surface quality was also influenced by the parameters of the machining process in the form of work-piece loadings and feed rates. This study revealed the higher rotation of the work-piece, the higher the value of the surface roughness. Based on the roughness class, the rotational parameters of the work-piece for 350 rpm with a feed speed of 0.051 mm that was good parameters in this study, which resulting the lowest surface roughness average value of 2.439 μm.Keyword : Turn-milling, orthogonal turn-milling, rotation, feed, roughness.